Exploring methodology to evaluate a heritage district from the architectural perspectives in relation to palaces, religious buildings and mausoleums in Kuala Kangsar district, Perak, Malaysia - Salleh, Nurul Hamiruddin; Mansor, Mazlina; Mahamod, Lukman Hakim; Kamaruddin, Zumahiran; Ab Latip, Nurul Syala (IIUM Press, 2019)
Preservation and conservation of heritage sites is an essential effort to achieve sustainable development in Malaysia. However, due to rapid development, many heritage sites and buildings are at risk around the world including Malaysia where many developments encroach into heritage sites and diminish the traces of our culture and history that are embedded in these sites. Eventually, these traces that are important for the identity and sense of place of a particular area and crucial in the educational and cultural development of a nation may be lost. The aim of this research is therefore to explore and examine the methodology to evaluate Kuala Kangsar as a Heritage District from the selected architectural attributes. Kuala Kangsar is chosen as a case study to test the methodology. Employing qualitative method, this research documented and examined the palaces, religious buildings and mausoleums in Kuala Kangsar district on its heritage values through field observation, contents analysis and interviews. All the identified attributes are marked within the related grids in the GIS map of Kuala Kangsar district that has been divided into 2,711 grids according to 1 km x 1 km grid. The findings from this research concluded that Kuala Kangsar cannot be declared as a Heritage District from the architectural perspectives in relation to palaces, religious buildings and mausoleums.